National character research paradigms - Polomoshnov, Andrey F.; Lavrukhina, Irina M.; Glushko, Irina V.; Maslova, Ekaterina S. (Opción, 2019)
The study objective is to analyze various approaches to the national identity problem.The leading research method is paradigmatic analysis of various conceptual and disciplinary approaches to the studies of both national character and identity of ethnic communities.As a result, the empirical and sociological paradigm stresses particular mechanisms of personal ethnic and national identification as well as the interaction of ethnic identity with other identity types, in particular social institutions and groups studied with the methods of experimental sociology. In conclusion, the integration function is the most adequate for interpretation of national identity under the philosophic and cultural paradigm.